Politeness Strategies Instagram Account @bdg.dukcapil In Responding to Comments - Merlina, Tina; Leksmana, Kusnadi Kibet (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This research aims to determine politeness strategies Instagram account @bdg.dukcapil in responding to comments. Researchers took data from some comments on the Instagram account @bdg.dukcapil which were replied to by the @bdg.dukcapil account. This research is a qualitative research. To analyze the politensess strategies, researchers used the theory of Brown and Levinson. The results of the research show that Instagram account @bdg.dukcapil using positive politeness strategies and negative politeness strategies in responding to comments from commentators. It is hoped that this research provide input for the Bandung Disdukcapil Instagram account to develop ways to respond to comments from commentators. Other objects such as products, figures, or influencers, and news can be used for further research.